Creating Special Purpose Nonprofits to Lessen the Cost of Public Infrastructure. (July 2019) - Bryce, Herrington J.
From a policy, practice, and theoretical perspective, this article promotes the use of the nonprofit to lessen the financial burden on government in advancing the wellbeing of the general public. The burden in this article is the cost of providing critical physical infrastructure for the benefit of an entire population or jurisdiction. How can the nonprofit materially lessen this financial burden? How may the trade-off between government agency appropriations and tax expenditures to nonprofits favor the use of a nonprofit? What about accountability to citizens and to government-why is this not an obstacle? Why is the nonprofit a versatile design for the provision of infrastructure either singularly or in any combination of public- private partnership? Why should this strategy be embraced if infrastructure requires a large upfront and continuous flow of cash and debt? Could this strategy bring infrastructure online quicker and at a lower government cost?